Learning the language of scripture: origen, wisdom, and the logic of interpretation - James, Mark Randall (Studies in Systematic Theology, 2021)
In Learning the Language of Scripture, Mark Randall James develops a pragmatically-inflected approach to the theological interpretation of scripture that draws on Origen's recently discovered Homilies on the Psalms.